Power Kader Posyandu dalam Membangun Health Literacy Masyarakat - Insana, Dinia; Swastikawara, Sinta (Universitas Brawijaya, 2021)
Posyandu cadres as non-professional health workers under the supervision of the Community Health Center have an important role in building and developing health programs through health promotion. In carrying out health promotion, cadres need to plan effective communication strategies to influence and change people's behavior. This research seeks to identify the power used by cadres as a strategy in carrying out health promotion. This research is qualitative research using the case study method. Data collection was carried out using purposive sampling and snowball sampling techniques at Posyandu Wijaya Kusuma, Banjararum Village, Singosari District, Malang Regency. Based on the data findings, cadres are seen as village health promoters whose task is to improve the welfare of the community by building their health literacy. Cadres carry out health promotion with approaches at the interpersonal and societal levels, power-over, and relational control. Through this strategy, cadres are able to build public health literacy at a critical literacy level.